Species-specific detection of inter-populations of Ditylenchus destructor - LIU Bin; MEI Yuan-yuan; ZHENG Jing-wu (浙江大学学报. 农业与生命科学版, 2007)
PCR-RFLP of rDNA ITS regions of seven geographic populations of D. destructor were made, and the variation in the sequence length and digestion patterns among intra-species populations was detected. According to the sequence character of the ITS region of rDNA of D. destructor, a pair of specific primers were designed, and effectiveness was proved by specific amplifying the corresponding ITS region of all the D. destructor populations. To test the sensitivity of the primers, one to five adult and juvenile specimens of D. destructor were chosen for specific amplification. All the D. destructor populations yielded a specific fragment with the length of 346 bp, and the inter-genus species had no specific amplification. The target fragment was also amplified with 1 to 5 adult specimens and 4 to 5 larva specimens of D. destructor. It is indicated that the primers designed for specific detection of D. destructor were steady, specific and sensitive, and the procedure was fast.